CULTURE SHOCK EXPERIENCED BY ENGLISH NATIVE SPEAKER: A CASE STUDY OF AN AMERICAN IN MAKASSAR - Serliah Nur; Aryana Nurul Qarimah; Karina Yunita Utari (UIN Alauddin Makassar, 2021)
Culture shock will happen when persons visit new place or country that they have never been before. They will get anxious because they do not speak the language, know the custom or understand people in their daily life. It couldhappened everywhere to everyone. Makassar as one of region in Indonesia is not known as tourist destination and it could lead the more potential to get in culture shock. Thus, this research studied about culture shock experienced by English native speakers in Makassar by using the theory of culture shock. Having done the interview and using the qualitative method in analyzing the data, this research finds that the culture shock experienced by English native speaker in Makassar is described in three phases of culture shock: anticipation, culture shock and adjustment. Moreover, the native English speaker finds more than self-healing in adjustment phase.